Determination of Rooting Rates of Rootstock Hazelnut (Corylus colurna L.) Genotypes in Wood Cuttings - Çolak, Salih; İslam, Ali; Turan, Ali; Yılmaz, Muharrem; Karagöl, Selim; Ayan, Sezgin (Karadeniz Fen Bilimleri Dergisi, 2025)
The research was conducted in Tosya district of Kastamonu province between 2020 and 2022 with the objective of ascertaining the rooting of rootstock Corylus colurna L. genotypes. The study utilized one-year-old cuttings, meticulously planned in three replicates, with 20 cuttings employed in each replicate. The doses of indole-3-butyric acid (IBA) employed for rooting ranged from 0 to 6000 ppm, with specific concentrations including 0, 500, 1000, 2000, 3000, 4000, 5000 and 6000 ppm. Two-thirds of the IBA-treated cuttings were then buried in pans containing a perlite, and rooting was induced. The traits of the survival rate (%), callusing and rooting rate (%), as well as rooting (quantity), roots (cm) and shoots length (cm) and the number of leaves (quantity), were examined. The study revealed that the highest rooting rate was observed in the 5000 ppm treatment, reaching 25%, while the lowest rate was recorded in the control, at 1.7%. The 1000 ppm treatment resulted in the highest number of roots (8%), followed by the 2000 ppm treatment, which produced 6.3%. Following a thorough evaluation of the study's findings, it is recommended that 5000 ppm IBA be applied for the purpose of rooting in wood cuttings.